Ageing of the Aboriginal and Torres Strait Islander population: numerical, structural, timing and spatial aspects - Jeromey B. Temple; Tom Wilson; Andrew Taylor; Margaret Kelaher; Sandra Eades (Elsevier, 2020)
Abstract Objectives: To assess levels of numerical, structural, timing and spatial aspects of ageing of the Aboriginal and Torres Strait Islander population. Methods: Population projections for 15 Australian regions were created by a multi‐state cohort‐component model. Results: The older (45‐plus) population grew from 29,815 in 1986 to 167,259 in 2016. In the subsequent 30 years, we project growth to 448,785 people. Growth rates of the older population vary: from 200% in the 60-64‐year‐old group to 800% growth in the 85‐plus age group by mid‐century. This strong numerical ageing is reflected in a shift in structural ageing by about six percentage points. Selected areas outside of capital cities are structurally older than many cities. Numerical ageing is strongest in capital cities and New South Wales. Cohort flow is the primary driver of ageing. Conclusions: Numerical and structural ageing is projected to increase significantly to mid‐century with important spatial variations. Population ageing is largely irreversible. Implications for public health: High numerical growth in the older Aboriginal and Torres Strait Islander population poses implications for increased demand for a range of health and care services. Variations in spatial and timing aspects of ageing indicate demand will peak earlier in some geographical locations relative to others.